Development of a semi-automated drip irrigation system to enhance water productivity and tuber yield of Gajah cassava under rainfed conditions - Hasbi, Muhammad; Darma, Rahim; Akzar, Rida; Nishantha, Busige; Bakheet Ali, Hamed Noralla; Mohd Nawi, Nolila; Maulidyah, Nurul; Abdul Syakur, Kemal (Society for Innovative Agriculture, University of Agriculture, 2025)
Cassava productivity in rainfed tropical regions is declining due to prolonged dry seasons and increasingly unpredictable rainfall patterns. In this study, we address these challenges by evaluating the application of a semi-automatic drip irrigation system combined with earlier planting times in the dry season. The goal is to increase yields and water use efficiency (WUE) in Gajah cassava varieties. In this field research, two treatments were compared: (P1) planting at the beginning of the dry season with drip irrigation support during the vegetative phase, and (P2) planting at the beginning of the rainy season conventionally without irrigation. Results showed that P1 significantly outperformed P2, achieving a 42.4% higher yield (110.95 tons/ha vs. 77.94 tons/ha) and a 34% improvement in WUE (4.896 kg/m³ vs. 3.654 kg/m³). In treatment P1, supplemental irrigation only covered 2.84% of the total water input, indicating its efficiency in mitigating early drought stress and supporting initial crop growth. Statistical analysis showed a significant difference in yield (p < 0.05), with P1 showing a higher response despite greater variability. These findings support the implementation of precision agriculture strategies that integrate planting schedules with seasonal rainfall patterns and targeted irrigation use. The semi-automated system, powered by solar panels and grid electricity, provides a scalable, cost-effective solution, particularly suitable for small-scale farmers in semi-arid and hilly areas. Future research should assess the long-term effects across agroecological zones. Additionally, irrigation protocols need refinement for different cassava growth stages. This integrated approach contributes to climate-smart agriculture by improving resource efficiency, crop resilience, and sustainability in water-limited environments.